1. Laser evoked potential in clinical practice: The diagnostic field in small fiber neuropathy. Issue 12 (December 2017) - Devigili, G.; Rinaldo, S.; Lettieri, C.; Eleopra, R.
Abstract : Small fiber neuropathy (SFN) is frequently encountered in clinical practice. Due to the small nerve fiber characteristics, the diagnosis requires the use of not conventional tests like skin biopsy, Quantitative sensory testing (QST) and Laser Evoked Potentials (LEPs). The aim of this study was to evaluate the diagnostic value of A-delta LEPs in clinical practice in a large cohort of patients with diagnosis of "definite" SFN. We screened 296 patients evaluated in our institution with confirmed diagnosis of sensory neuropathy. We collected 140 patients with pure SFN and 79 patients with mixed fiber neuropathy (MFN). All underwent clinical evaluation, sensory, painful thermal and mechanical detection thresholds, and quantification of somatic intraepidermal nerve fibers (IENF) by skin biopsy to define the diagnosis. Then, all SFN and MFN patients underwent LEPs. The sensitivity and specificity were calculated compared with our normative data on 67 healthy age-matched subjects. A-delta LEPs at dorsal foot showed 76% sensitivity and 80% specificity in SFN diagnosis, and, if performed bilaterally, the sensitivity and specificity increased (81% and 84%). We did not find any correlation between LEPs and entity of skin denervation, but we found good concordance with warm, heat pain thresholds and pinprick perception.